Salinity Resistance of Six Amaranth (Amaranthus sp.) Cultivars Cultivated in Benin at Germination Stage - Wouyou, Agapit; GANDONOU, GBOSSÈGNON CHRISTOPHE BERNARD; MONTCHO, David; KPINKOUN, Julien; KINSOU, Eliane; ASSOGBA KOMLAN, Françoise; GNANCADJA, ANDRÉ LÉOPOLD SIMPLICE (My University, 2016)
Aims: In this study, salt resistance level of six amaranth (Amaranthus sp.) cultivars including five from Amaranthus cruentus species (AA-04-028, AA-04-017, Locale, Rouge and Red-Sudan) and one from Amaranthus graecizans species (Stem2-Sat2) cultivated in Benin was evaluated at the germination stage. Study Design: The experiment was laid out as a Randomized Complete Block Design (RCBD),with four replications. Place and Duration of Study: The experiment was carried out in the Plant Physiology. and Abiotic Stresses Study of University of Abomey Calavi, Republic of Benin from September to October 2015. Methodology: Seeds were submitted to treatment with five NaCl concentrations (0; 30; 60; 90 and 120 mM NaCl) in petri dishes. Seed germination was checked every day during the ten days incubation period. Germination percentage was determined within 10 days incubation. Four replicates of 50 seeds each were used. Results: From day 2 to day 10, NaCl delayed seed germination rate proportionately to NaCl concentration. Salt stress reduced the rate of germination and the germination index in all cultivars. At the end of the 10th days, salt stress significantly decreased the rate of final germination for all cultivars investigated whatever the NaCl concentrations used, except for cultivar Red Sudan and Rouge which showed a slight stimulation of germination at 30 mM NaCl. However, the NaCl stress effects on seed germination of the six cultivars were significantly variable. The average reduction due to NaCl stress was 22.11%; 20.90%; 17.28%; 15.58%; 8.03% and 6.57% for AA-04-017, AA- 04-028, Rouge, Locale, Stem2-Sat2 and Red-Sudan, respectively. Conclusion: NaCl stress delayed seed germination and reduced the germination index and the rate of final germination. Among the six cultivars, Red-Sudan appeared to be the most salt resistant. For the first time, we demonstrated that there is a variability of relative salt-stress resistance among Amaranthus cruentus cultivars at germination stage.
Keywords: Amaranthus cruentus; cultivars; germination; salt-resistance